Electronic Learning Network (ELN) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Electronic Learning Network (ELN) brings together women professionals, male colleagues and women farmers in Africa working in partnership for food security and environmental sustainability.